2021
DOI: 10.1002/phar.2505
|View full text |Cite
|
Sign up to set email alerts
|

A guide to therapeutic drug monitoring of β‐lactam antibiotics

Abstract: Pharmacists play an important role in assessing, managing, and monitoring the efficacy and safety of medications. A common avenue for accomplishing this responsibility is through therapeutic drug monitoring (TDM) of many drugs, a duty that has been successfully managed by pharmacists for over four decades. 1,2 Antimicrobials, including aminoglycosides, vancomycin, voriconazole, and historically, chloramphenicol and quinidine, have been frequent candidates for pharmacist-led TDM. Antimicrobial TDM has tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 102 publications
(198 reference statements)
0
59
0
Order By: Relevance
“…While Bayesian methods can estimate more accurate PK profiles for individual patients, the use of first order equations is a reasonable and practical alternative to determining target attainment. 32 Our sampling times were all during the post-distribution phase, samples were collected at steady-state, and the precise timing of sampling was recorded, minimizing bias of this approach. Further, to our knowledge, no currently available Bayesian dosing software programs incorporate pediatric PK models for FEP.…”
Section: Discussionmentioning
confidence: 99%
“…While Bayesian methods can estimate more accurate PK profiles for individual patients, the use of first order equations is a reasonable and practical alternative to determining target attainment. 32 Our sampling times were all during the post-distribution phase, samples were collected at steady-state, and the precise timing of sampling was recorded, minimizing bias of this approach. Further, to our knowledge, no currently available Bayesian dosing software programs incorporate pediatric PK models for FEP.…”
Section: Discussionmentioning
confidence: 99%
“…As the β-lactam antibiotics are time-dependent antimicrobial agents, the duration that the free (protein unbound) antibiotic concentration is greater than the minimal inhibitory concentration (MIC) (f T >MIC ) determines microbicidal efficacy [38]. For critically ill patients, the recommended pharmacodynamic (PD) target for the β-lactams is at least 100% f T >MIC for the given pathogen [39].…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin and β-lactams are the antibiotics most frequently used and measured in plasma in the intensive care unit (ICU) setting, because of their antimicrobial spectrum and their PK/PD characteristics [7,8]. Vancomycin TDM and its use in continuous or prolonged infusion (PI) could have a beneficial effect in reaching PK targets and reducing nephrotoxicity and renal replacement therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…With reference to β-lactam's TDM literature status, studies have shown positive results in terms of clinical cure rates (the reduction of procalcitonin in patients with TDM follow-up), a shorter mean duration of invasive ventilation, the achievement of PK parameters and an easier dose guidance process, particularly in critically ill patients or patients undergoing renal replacement therapy [7,[11][12][13][14][15][16]. More clinical studies should be developed to demonstrate the conclusive benefits of this practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation